2020
DOI: 10.1159/000510792
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hyperbaric Oxygen Therapy on Rectal Ulcers after Argon Plasma Coagulation

Abstract: Chronic radiation proctitis usually develops 3 months after therapy. Despite the lack of standard guidelines regarding treatment, argon plasma coagulation is often a safe and effective endoscopic therapy. However, rectal ulcers are a common complication after argon plasma coagulation. Nevertheless, most patients are asymptomatic and do not require additional monitoring or treatment. We report a case of an argon plasma coagulation-induced ulcer with relevant symptoms and refractory to medical treatment. The pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The lack of guidelines for the optimal APC settings (method of application, time between sessions, and flow rate) may lead to a higher number of APC-induced ulcers. According to Sato et al [5] prevention of damage of the deeper underlying muscle layer, while maintaining an effective submucosal telangiectasia treatment, occurs with the lowest effective dose of 40 W with 1.2 L/min of gas flow and a coagulation time of 2 s. In both our case and that of Laranjo et al [1], the dose and flow applied were adequate, but the time of coagulation was not taken into consideration. The latter may have been the culprit for the development of the APC-induced ulcers.…”
mentioning
confidence: 47%
See 3 more Smart Citations
“…The lack of guidelines for the optimal APC settings (method of application, time between sessions, and flow rate) may lead to a higher number of APC-induced ulcers. According to Sato et al [5] prevention of damage of the deeper underlying muscle layer, while maintaining an effective submucosal telangiectasia treatment, occurs with the lowest effective dose of 40 W with 1.2 L/min of gas flow and a coagulation time of 2 s. In both our case and that of Laranjo et al [1], the dose and flow applied were adequate, but the time of coagulation was not taken into consideration. The latter may have been the culprit for the development of the APC-induced ulcers.…”
mentioning
confidence: 47%
“…We read with great interest the paper by Laranjo et al [1] entitled "The Effect of Hyperbaric Oxygen Therapy on Rectal Ulcers after Argon Plasma Coagulation." The authors reported the case of a patient with chronic radiation proctitis, who developed rectal ulcers after endoscopic treatment with argon plasma coagulation (APC) and was successfully treated with hyperbaric oxygen therapy (HBO).…”
Section: Dear Editormentioning
confidence: 99%
See 2 more Smart Citations
“…Among pharmacological regimens, formalin application (4-10%) has been demonstrated to be an effective medical treatment ( 8 , 23 , 25 – 28 ), as well as sucralfate enemas ( 6 , 23 , 29 ), and metronidazole combined with ciprofloxacin ( 20 , 29 ). Argon plasma coagulation (APC) is the first-line endoscopic strategy for individuals with hemorrhagic RIP ( 24 , 29 31 ). Surgery is generally reserved for advanced stages of RIP refractory to optimal medical and endoscopic therapies ( 8 , 30 ).…”
Section: Introductionmentioning
confidence: 99%